Empreendedorismo digital: entre condições estruturais empreendedoras, autoeficácia e transposição de barreiras - Costa, José Lucas Brandão (2024)
Digital entrepreneurship, in recent years, has emerged as a market trend. There are many benefits of entrepreneurship digitally, however, there are considerable challenges to be faced by those who seek to undertake business through digital platforms. To alleviate this type of situation, the Global Entrepreneurship Monitor - (GEM) proposed the Structural Conditions of Entrepreneurship (CEEs), which are directly linked to entrepreneurial activities and aim to present the main factors that highlight those who seek to undertake overcoming obstacles. Research by Molina-López et al. (2021), carried out in Spain and exclusively with digital entrepreneurs, confirmed the importance of CEEs in overcoming barriers to establishing female digital businesses. This relationship was being mediated by the perception of entrepreneurial self-efficacy. Studies that address the barriers in the process of creating digital companies are still needed. Thus, Molina-López et al. (2021) proposes the expansion, improvement and consolidation of the model they developed before entrepreneurs of both sexes (female and male). Given this gap, the present study obtained the effects of the relationship between entrepreneurial structural conditions (CEEs), entrepreneurial self-efficacy (AUTEF) and overcoming barriers (BADIG), in the development process of digital companies in the Brazilian Northeast. This research is classified as descriptive, quantitative in nature and cross-sectional. Data collection took place through an online survey, using a questionnaire that was prepared on the Google Forms platform, which was applied to 170 digital entrepreneurs from northeastern Brazil. To select these individuals, the non-probability accessibility sampling technique was used. The data were analyzed using descriptive statistics tests and multivariate analysis techniques, using Excel and SmartPLS 4.0 statistical software. The research findings confirmed that entrepreneurial structural conditions enable a significant and positive effect on overcoming barriers to digital entrepreneurship. Entrepreneurial structural conditions had a positive and significant effect on the perception of entrepreneurial self-efficacy. The perception of self-efficacy, in turn, has a positive and significant effect on overcoming barriers in digital ventures. Finally, it is also concluded that there is a mediation relationship between the paths of the CEE→ AUTEF→ BADIG constructs, indicating that the CEEs, when mediated by selfefficacy, enable a positive effect in overcoming barriers; This effect is more significant than that which occurs in the direct relationship between CEE→ BADIG. This leads us to believe that the effect of entrepreneurial structural conditions is low when it is directly linked to the process of overcoming barriers to entrepreneurship in the digital world.